Degrees of Psychological Well-Being among Students of Palestinian Universities in Hebron Governorate - Nabeel I. Al Jundy; Jbarah A. Talahmeh (Sultan Qaboos University, 2017)
This study aims at investigating the levels of psychological well-being among Palestinian university students in Hebron District, and adapting Ryff's Psychological Well-being Scales to the Palestinian environment, The researchers applied the Ryff's Psychlogical Well-being Scales on a simple random sample of (200) students located at three Palestinian universities (Hebron University, Al-Quds open University, & Polytechnic University). Validity was confirmed. Moreover, the reliability of the scale was confirmed by using Cronbach a coefficient. The study concluded that the degrees of Palestinian students' psychological wellbeing were moderate. In addition to that, the study found that there were differences in the degree of psychological well-being according to gender in favor of females, differences according to the type of specialization in favor of students in the human colleges, differences due to the economic level in favor of students with higher incomes, and differences due to the place of residence in favor of villagers students. Furthermore, the study found there were no differences in the average psychological well-being due to the sitting university. Finally, the study has come out a set of recommendations stemming from its results, such as the need to address welfare for Palestinians, especially in crowded cities, as well as the need to motivate university students in science faculties, and to reduce the degrees of tension induced by the difficult context in which Palestinians live.